1972
DOI: 10.1111/j.1744-7348.1972.tb05084.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic action of benomyl against late‐wilt disease of maize.

Abstract: SUMMARYBenomyl (methyl‐I‐(butyl carbamoyl)‐2‐benzimidazole carbamate) at 2.5 to 100 ppm completely inhibited the growth in vitro of Cephalosporium maydis Samra, Sabet & Hingorani, the causal fungus of late‐wilt of maize. In pot experiments, late‐wilt was controlled by applications equivalent to 10 ppm benomyl/unit wt dry soil at sowing but not by applications 30 days after sowing or by seed treatments (dusts and dips). A fungitoxic substance was detected in benomyl‐treated soil, planted with maize, 120–150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The method of assaying the effect of fungicides on the pathogen in a series of trials starting in a petri dish plate assay, followed by detached root and resulting in a seedlings pathogenicity assay, using molecular and morphological approaches presented here should be addressed in a critical manner but it has several advantages. In the past, many attempts were made to eradicate the pathogen using chemical and biological methods [31][32][33][34][35][36]. Some fungicides tested worked well in pots but failed in field experiments [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method of assaying the effect of fungicides on the pathogen in a series of trials starting in a petri dish plate assay, followed by detached root and resulting in a seedlings pathogenicity assay, using molecular and morphological approaches presented here should be addressed in a critical manner but it has several advantages. In the past, many attempts were made to eradicate the pathogen using chemical and biological methods [31][32][33][34][35][36]. Some fungicides tested worked well in pots but failed in field experiments [32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was found that systemic fungicide Benomyl (methyl 1-(butylcarbamoyl) benzimidazol-2-ylcarbamate, CAS no. 17804-35-2) at 2.5 to 100 ppm concentration completely inhibits late wilting disease in pots (seed treatment is not effective), but the application of 10 kg Benomyl/4200 m 2 in the field failed to prevent the disease [34]. In contrast, AbdEl-Rahim and colleagues (1982) found that the systemic Benylate fungicide (benzyl benzoate, CAS no.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a much longer lasting protection resulted from soil treatments without the plants being transferred after treatment (Tramier and Antonini, 1971). Because of its extreme persistence in soils (and in plant tissues) (Hock et al, 1970;Jacobsen and Williams, 1970;Netzer and Dishon, 1970;Schreiber et al, 1971 ;Riesselman and Weihing, 1972;Sabet et al, 1972) benomyl can often completely protect plants for many months, sometimes for up to 3 years after its application (Biehn and Dimond, 1971;Biehn, 1973). This residual activity of benomyl might imply that a single application to the soil might be effective over several successive crops (Jacobsen and Williams, 1970).…”
Section: Discussionmentioning
confidence: 97%
“…Small-scale experiments with systemic fungicides have demonstrated more or less effective control of a number of vascular diseases, including Verticillium wilts of cotton (Erwin, Sims & Partridge, 1968 ;Ranney, 1971 ; Booth, Rawlins & Chew, 1g72), tomato (Ebben, 1970), tobacco (Hartill, 1972), potato (Biehn, 1970), carnation (Ebben, 1971; Tramier & Antonini, 1971), lucerne (Dixon, 1972), strawberry (Jordan, 1972; Lockhart, Macnab & Bolwyn, 1969;Miiller, 1972) and chrysanthemum (Besemer, McCain & Paulus, 1969); Fusarium wilts of tomato and watermelon (Thanassoulopoulos, Giannopolitis & Kitsos, 1970); Dutch elm disease (Biehn & Dimond, 1971 ;Smalley, 1971) and late-wilt (Cephalosporium maydk) of maize (Sabet, Samra & Abdel-Rahim, 1972). However, as a means of controlling vascular diseases in commercial practice in the field the systemic fungicides have proved valuable only to a limited extent, apparently for two main reasons; treatments tend to be less effective in the field than in laboratory and glass-house experiments, a problem that is not necessarily resolved by increasing the dose-rate in the field, and the cost of the chemicals and of the labour required for their application may exceed the value of the increase in crop that results from control of the disease.…”
Section: Introductionmentioning
confidence: 99%